Pengaruh Pernikahan Dini terhadap Kesejahteraan Rumah Tangga - Mitha Rafina; Sinta Sinta; Oza Salsa; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Early marriage is a complex issue that affects household welfare in various aspects. Social, economic, and cultural factors often trigger early marriage, especially in Indonesia. The negative impacts of early marriage can include limited access to education and job opportunities, increased risk of domestic violence, reproductive health problems, and difficulties in raising children. Therefore, research on the influence of early marriage on household welfare is crucial to find effective solutions to reduce its negative impacts. This research uses a library research method by collecting data from various related literature, such as books, scientific journals, and credible previous research. Critical and in-depth analysis is conducted on the literature to gain a comprehensive understanding of the research topic and build strong, evidence-based arguments. Thus, this literature study becomes a solid foundation for the research. The results show that early marriage is a complex issue that affects household and individual welfare. Factors such as education, knowledge, accidents, relationship consolidation, customs, parental and child attitudes, economy, self-will, and mass media can encourage early marriage. The impacts of early marriage are widespread, including anemia in pregnant adolescents, loss of educational opportunities, limited social interaction, domestic violence, and reproductive health problems. Therefore, preventing early marriage is crucial through formal education, sex education socialization, empowering communities, increasing government roles, and promoting gender equality. By doing so, it is expected to reduce the negative impacts of early marriage and improve individual and household welfare.